EDUCATIONAL USE OF VIDEO AND COMPUTER EQUIPMENT - Гудз, І. М.; Геник, С. М.; Михальчук, Д. С.; Симчич, А. В.; Гудз, О. І.; Грицюк, Т. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents the results of many years of experience using at the Chair of General Surgery of computer equipment and direct video broadcasting of the operating room of vascular surgery department for the students of Medical Faculty (specialty "Medicine" and "Pediatrics") and Foreign Citizens Training Faculty of IFNMU for the disciplines: "Care for the surgical patients (practice of the care of the surgical patients)" – 2nd year, "General surgery" - 3rd year; "Main duties and professional actions of a nurse of the surgical department (nursing practice in surgery) " – 3rd year; Thematic module "Vascular Surgery" – 5th year; "Surgery" – 6th year. Significant benefits of practical classes involving computer technology and video direct broadcasting of the operating room to provide pedagogical process have demonstrated .